D-O-A based organic phosphors for both aggregation-induced electrophosphorescence and host-free sensitization - Lulin Xu; Yuhang Mo; Ning Su; Changshen Shi; Ning Sun; Yuewei Zhang; Lian Duan; Zheng-Hong Lu; Junqiao Ding (Nature Communications, 2023)
Pure organic room-temperature phosphorescencent materials draw much attention but realising electroluminescence under electric excitation is challenging. Here the authors propose a donor-oxygen-acceptor molecular design realizing aggregation-induced organic room-temperature electrophosphorescence with high external quantum efficiency.